Formation and chemistry of carboxylic anhydrides at the graphene edge. Issue 126 (10th December 2015) - Rosillo-Lopez, Martin; Lee, Tai Jung; Bella, Malika; Hart, Martin; Salzmann, Christoph G.
Abstract : Carboxylic anhydrides exist in dynamic equilibrium with carboxylic acid groups at the graphene edge. These can be used for chemical functionalization with amine nucleophiles in a simple, straight-forward manner. Abstract : Using graphene for a wide range of applications often requires delicate chemical processing and functionalisation. Here we first report the synthesis of graphene nanoflakes with carboxylic acid groups at the graphene edges from multi-wall carbon nanotube materials. Using this material we then show that highly reactive carboxylic anhydride groups exist in dynamic equilibrium with the carboxylic acids in aqueous dispersion. Heating in vacuum shifts the equilibrium as about 80% of the carboxylic acid groups transform to the anhydrides. These new insights into graphene chemistry enable us to develop a simple, straight-forward chemical functionalisation protocol for graphene making use of the anhydrides. The graphene nanoflakes were found to react readily with amine nucleophiles in aqueous dispersion to yield the corresponding amides. The new protocol allows us to alter the zetapotential of the graphene nanoflakes and to decorate the graphene edges with gold nanoparticles. Due to its simplicity, we expect this procedure to find wide-spread use in the chemical functionalisation of graphene and to enable new graphene-based applications.